Antitumor proteinkinase inhibitor imatinib may be regarded as a potential correcting agent for COVID-19 associated pulmonary fibrosis - I. N. Mikhaylova; N. M. Treshalina; I. Zh. Shubina; I. V. Manina; M. V. Kiselevsky; A. N. Lukashev (Успехи молекулярной онкологии)
Imatinib mesilate is a well-known antitumor target inhibitor of protein tyrosine kinase, which is effective in different cancer types expressing Bcr / Abl and, in particular, in hemoblastosis. A higher interest to imatinib during the COVID-19 epidemic is explained by the fact that cancer patients are one of the COVID-19 risk groups. Moreover, imatinib target mechanism of action, which is effective in cancer, can have a high potential against the most severe COVID-19 complication such as the disease associated pulmonary fibrosis. COVID-19 associated interstitial pulmonary fibrosis develops as an autoimmune process caused by systemic inflammation with atypical (idiopathic) pneumonia resulting from acute respiratory distress syndrome with the tyrosine kinase mechanism of signaling pathway activation and cellular response. Experi-mental and clinical results showing antifibrotic and dose-related antithrombotic imatinib effect demonstrate perspective use of this antitumor agent to correct COVID-19 associated pneumonia causing a high death rate of patients with COVID-19.The review presents literature data of 2001–2020 discussing pathologic genetic and clinical characteristics of the fibrosis which exacerbates COVID-19 pneumonia in adults. The sequence of the disease processes demonstrates that disease progression with the decreasing oxygen saturation in the peripheral blood intensifies local thrombosis in the lungs. As a result, hypoxia is developing, which is difficult to control and can cause lethal outcome in severe cases. Yet, the conventional antifibrotic and thrombolytic agents can only partially control the process of pneumofibrosis including that of cancer patients. The approximate antifibrotic dose of imatinib 400 mg / day is therapeutic for oncopatho-logy. The antitumor drug registered in many countries and well described side effects and contraindications needs no long-term registration studies for a new indication, therefore, it may be easily prepared for clinical testing.